On Optimal Tempered Lévy Flight Foraging - Chen, Yuquan; Hollenbeck, Derek; Wang, Yong; Chen, YangQuan (Frontiers in Physics, 2018)
Optimal random foraging strategy has gained increasing attention. It is shown that Lévy flight is more efficient compared with the Brownian motion when the targets are sparse. However, standard Lévy flight generally cannot be followed in practice. In this paper, we assume that each flight of the forager is possibly interrupted by some uncertain factors, such as obstacles on the flight direction, natural enemies in the vision distance, and restrictions in the energy storage for each flight, and introduce the tempered Lévy distribution p(l)e^-ρ ll^-μ. It is validated by both theoretical analyses and simulation results that a higher searching efficiency can be achieved when a smaller ρ or μ is chosen. Moreover, by taking the flight time as the waiting time, the master equation of the random searching procedure can be obtained. Interestingly, we build two different types of master equations: one is the standard diffusion equation and the other one is the tempered fractional diffusion equation.